Dust pollution in construction site / Mohammd İkmar Firdaus Johari and Zalida Salleh - Johari, Mohammd İkmar Firdaus; Salleh, Zalida (2018)
Dust pollution that occurs in the environment is caused by poor air quality that is not monitored well in the construction industry during the construction process. The construction industry is a major source of pollution responsible for about 4% of particulate emission. This paper aims to study dust pollution in the construction industry in Malaysia, particularly looking at its impacts on human health and the methods used to control dust in the construction site. Data collected in this study were analyzed using triangulation method. The findings indicate that construction workers believed dust does give impact to body health problem and the most common method found to control dust is watering system. This study focus to impacts dust pollution in the construction site to human health and identify the methods that used to control the dust pollution in the construction site. It is hoped that the findings of this study would create awareness on the impact of dust and recommend a method that would best control dust in construction sites